A retrospective study of baseline peritoneal transport character and left ventricular hypertrophy in incident peritoneal dialysis patients: interrelationship and prognostic impacts. Issue 1 (31st December 2022) - Wang, Yi; Huang, Guansen; Ma, Xiaoyan; Zang, Xiujuan; Bai, Shoujun; Wang, Yakun; Du, Lin; Lv, Zexin; Li, Jinqing; Chen, Hui; Hu, Yan; Shi, Yingfeng; et al.
Abstract: Background: Left ventricular hypertrophy is associated with adverse outcomes among peritoneal dialysis patients. The aim of this study was to evaluate the prognostic impact of baseline left ventricular hypertrophy and its relationship with baseline peritoneal transfer characteristics in peritoneal dialysis patients. Methods: We enrolled 151 incident peritoneal dialysis patients to perform a multicentric retrospective cohort study since January 1, 2017 to January 31, 2021. Patients were grouped based on baseline dialysate-to-plasma creatinine ratio at 4 h as follows: low (<0.50), low average (0.5–0.64), high average (0.65–0.80) and high (≥0.81). Echocardiography and clinic data were recorded yearly. The Cox proportional hazards models and competing risk model were used to evaluate patients' survival. Generalized linear mixed models were performed to explore risk factors associated with left ventricular hypertrophy. Results: During a median follow-up period of 33 months (range, 16–48 months), 21 (13.9%) patients died, including 16 (10.60%) cardiovascular deaths. Controlling the competing risks of switching to hemodialysis, kidney transplantation and loss to follow-up, baseline left ventricular hypertrophy was an independent risk factor for all-cause mortality (subdistribution hazard ratio, 2.645; 95% confidence interval, 1.156–6.056; p  = 0.021). Baseline high and high average transport status were positively related to left ventricular mass index and left atrium diameter 2 years after PD initiation. Conclusion: Baseline fast peritoneal solute transport rate may be an effect factor for aggravating left ventricular hypertrophy which predicted poor outcomes for peritoneal dialysis patients. The findings offered important ideas for further prospective intervention study.